Shiva Temple (Temple 3) in the Baroli Group of Tempes - Temples of India Project Team (Jio Institute, 2024)
Temple 3 in the Baroli group of temples is a Shiva Temple situated at the centre of a water tank. Due to its location within a tank, this temple is slightly lower than the other two temples. The tank has steps that lead to the centre, and a pathway on the east side provides access to the main entrance of the shrine.